Achados epidemiológicos de acidentes envolvendo motocicletas e ferimento por arma de fogo em Sobral-Ceará, atendidos pelo samu no período de 2019 a 2020 - Pereira, Diego Cesar da Silva Tavares (2022)
Currently, traffic accidents involving motorcycles are among the biggest problems faced by municipalities considered to be medium-sized. Another factor that is also migrating from large cities to smaller municipalities involves the issue of violence associated with occurrences with firearms. Therefore, these two factors can affect hospital care due to hospital beds, harming other patients who are on the waiting list for other types of surgery. In this sense, the objective of the present study was to analyze the spatial factors in the neighborhoods of Sobral associated with accidents involving motorcycles and firearm injuries in the years 2019 and 2020. The research was carried out in the database of the Medical Archive and Statistics Service (SAME) of SAMU, in Sobral - CE. To verify the existence or not of spatial patterns between the neighborhoods of Sobral, the Moran I local index and the kernel density surface were used. The local spatial empirical Bayesian rate was also used to smooth the gross rate in the analysis of occurrences. According to the results, accidents involving motorcycles had a unit decrease rate of 0.21, between the years analyzed, and this drop was largely due to Covid-19 with the restrictions on circulation resulting from the pandemic. It is also worth mentioning that the occurrences were concentrated in the streets of the city center and its surroundings and in the Junco neighborhood. The affected individuals were aged between 20 and 29 years, were male and the occurrences were concentrated between 12:00 and 18:00 hours, with the fall being the most frequent occurrence with non-fatal victims. On the other hand, the incidence with firearms, presents a spread throughout all the neighborhoods of Sobral, but a greater concentration can be highlighted in the neighborhood of Centro and Cidade Gerardo Cristino de Menezes. Unlike motorcycle accidents, this type of incident showed an increase in the unit rate of 1.26, with a predominance of the age group between 20 and 29 years, males and a prevalence of hours between 18:00 and 24:00. In this way, it was possible to conclude that there is a spatial inequality between the neighborhoods, accidents involving motorcycles are concentrated around the center neighborhood because it is a convergence zone for most services in the municipality of Sobral, and despite having shown a reduction in Due to the pandemic in 2020, and with that, it becomes important for municipal public agents to act through educational policies and awareness of bikers regarding primarily the use of helmets. Finally, due to the growth and spread of incidents involving firearms in Sobral, and due to the complexity of the problem, it is important to highlight, at the municipal level, the construction of public policies focused on the prevention of homicides in social groups that present greater socioeconomic vulnerability. Thus, it is highlighted that spatial data analysis techniques offer great capabilities for the production of new information. Occurrences due to external causes are influenced by human behavior, therefore, it is suggested to expand spaces for discussion on the subject, aiming at raising awareness of the population in general, as well as implementing strategies to minimize these accidents due to external causes.